Studying the effect of carbon powder addition on the performance of natural mucilage dra flowing in aqueous media - Sivalingam, Narendran (2010)
In the present studies, effect of carbon powder addition on the performance of natural mucilage DRA flowing in aqueous was identified and the performance of natural mucilage DRA flowing in aqueous media was optimized. Carbon powders were presented as a new effective Drag Reducing Agent to improve the performance of natural mucilage flowing in aqueous media. The effects of using various concentrations of fiber and flow rate on increasing the flow in pipelines were investigated in a fully developed turbulent flow and in various concentration of the natural polymer used. Natural polymer that used in the experiment is in the form of mucilage that extracted from okra, cocoa husk and halba respectively. A built experimental rig of PVC pipes was used in order to investigate the performance of carbon powder fiber as drag reducing agent. The experimental results showed that the carbon powder have a great ability to be a good reducing agent in aqueous media. The addition of carbon powder in the natural polymer in pipelines increase the drag reduction consistently and up to 65% from 35% when using natural polymer only. This reduction certainly improves the performance of DRA in the pipelines effectively and does have ability to be commercialized and marketed.